Olhar nos olhos da tragédia: a ressignificação de Medeia por Oduvaldo Vianna Filho: diálogos entre história e teledramaturgia - Steinbach, Amanda Maíra (2012)
Oduvaldo Vianna Filho, Vianinha, played an important role in the dramaturgical scene in Brazil. Exponent of so-called political theater of the 1960s and 1970s, he joined the Arena, the UNE's CPC and the Opinion Group. Versatile creator, his texts walk from comedy to farce, passing through the drama, and what can be observed in all of them is the full field of theatrical carpentry. This versatility has been extended to works produced in the emerging television networks in the country, which meant that in 1970 the author integrates the playwriting team of the already prominent Rede Globo. In Globo TV Network, Vianinha rethought, along with Armando Costa, the series The Great Family, and was author of some episodes of Special Cases program. His playwriting has been studied with increasing frequency in graduate programs in the country. What one observes, however, is that there is a preference for his theatrical drama, very few works being produced about his soap operas. The perception of this gap and the value of texts written for television, especially his adaptations of classical literature for the Special Cases program, underpinned the development of the dissertation presented here. Here we present and discuss the debate that the author embarked on mass culture in Brazil, seeking, from these testimonials, tips and explanations for his actions in that environment, despite his criticisms and his attachment to the PCB. Vianinha s voice is promoted by the intersection of the content of his interviews, his plays, whose characters are professionals of mass media, and the content of scripts designed by him. From the presentation of these scripts, we can see how the author transposed to the Brazilian universe texts designed in periods and societies very different from those in which he lived, an if he held or not the objectives pursued with its theatrical drama, which were representation and recovery of a typically popular culture and awareness of his public on problems that plagued Brazil of the "economic miracle". Among the screenplays written by Vianinha, one especially gratified him - to the point of considering it his best work in television - his adaptation of Greek tragedy, written by Euripides, Medea. Given the beauty of the text and its staging and the lack of analysis of the scene of his soap operas, we finished the job with a detailed analysis of the scene, highlighting the effectiveness of its staging to television language - which exposes the full fielding of the medium by the author - and the new possibilities of interpretation of his Jason, other than a vile traitor, perceived by the interpretive tradition of the original book and its adaptations over the centuries, detail that reveals one of the most valuable features of the author, his humanistic verve, born of his in depth perception about the Brazilian reality. So we tried to contribute to studies on the playwriting of Oduvaldo Vianna Filho and on the history of television in Brazil.